2007
DOI: 10.1523/jneurosci.2883-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Arc/Arg3.1 Synthesis Controls Long-Term Potentiation Consolidation through Regulation of Local Actin Polymerization in the Dentate GyrusIn Vivo

Abstract: New gene expression is necessary for long-term potentiation (LTP) consolidation, yet roles for specific activity-induced mRNAs have not been defined. Here we probed the dynamic function of activity-induced Arc (activity-regulated cytoskeletal-associated protein)/Arg3.1 (activity-regulated gene 3.1 protein homolog) mRNA using brief, local infusions of antisense (AS) oligodeoxynucleotides at multiple time points during dentate gyrus LTP in vivo. Surprisingly, early Arc synthesis is necessary for early expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
473
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(493 citation statements)
references
References 75 publications
20
473
0
Order By: Relevance
“…For example, the activity-regulated cytoskeletal-associated protein (Arc/Arg3.1), whose expression is known to be dependent on Akt-mammalian target of rapamycin activation, was found to regulate a-amino-3-hydroxy-5-methyllisoxazole-4-propionic acid receptor trafficking (103) . In agreement with this, the expression of Arc/Arg3.1 was shown to facilitate changes in synaptic strength and the induction of morphological changes, such as those dependent on actin-polymerisation (140,141) (Fig. 2(B)).…”
Section: Molecular Basis Of Memorysupporting
confidence: 70%
“…For example, the activity-regulated cytoskeletal-associated protein (Arc/Arg3.1), whose expression is known to be dependent on Akt-mammalian target of rapamycin activation, was found to regulate a-amino-3-hydroxy-5-methyllisoxazole-4-propionic acid receptor trafficking (103) . In agreement with this, the expression of Arc/Arg3.1 was shown to facilitate changes in synaptic strength and the induction of morphological changes, such as those dependent on actin-polymerisation (140,141) (Fig. 2(B)).…”
Section: Molecular Basis Of Memorysupporting
confidence: 70%
“…Messaoudi et al (11) reported that Arc protein synthesis was required for BDNF-induced LTP. Furthermore, two waves of Arc induction have been observed after a single spatial exploration (19).…”
Section: Discussionmentioning
confidence: 99%
“…Arc mRNA has been detected in cell bodies, dendrites, and spines after stimulation (7,8), and the Arc protein could be synthesized locally at dendritic spines (9,10). Arc is known to be required for the endocytosis of AMPA receptors (10) and for long-term potentiation (LTP)-induced F-actin stabilization (9,11). Okuno et al (12) reported that Arc plays a role in the inverse synaptic tagging of silent synapses; Arc accumulated in silent synapses to reduce surface AMPA receptors (12).…”
mentioning
confidence: 99%
“…Intrahippocampal infusion of BDNF resulted in the accumulation of Arc transcripts in dendrites and triggered long-term potentiation (BDNF-LTP) at medial perforant path-granule cell synapses in vivo (Messaoudi et al, 2007;Ying et al, 2002), and similar effects were observed in cultured cerebrocortical neurons (Rao et al, 2006), but the mechanisms involved have not been clarified. BDNF signaling induces the phosphorylation of ZBP1 and local synthesis of b-actin in growth cones, contributing to growth cone turning (Sasaki et al, 2010).…”
Section: Cis-acting Elements and Mrna Transport Into Dendritesmentioning
confidence: 99%